Endoscopic Third Ventriculostomy for the Management of Obstructive Hydrocephalus in Pregnancy: A Case Report and Review of the Literature - Durán-Ojeda, Alejandro; Campos-Fajardo, Santiago; Suárez-Monsalve, Silvia; Lindado-Pacheco, Carlos Alberto; Becerra-Ospina, Jaime Eduardo (Journal of Neurological Surgery Reports, 2024)
Introduction Hydrocephalus is a condition characterized by the abnormal accumulation of cerebrospinal fluid within the brain's ventricular system. It can stem from obstructive and nonobstructive causes. Pregnancy introduces physiopathological changes that may heighten the risk of developing or worsening symptomatic hydrocephalus. Nevertheless, comprehensive reports on this aspect, especially regarding surgical interventions, remain scarce.Case Report A young woman with a history of recurrent headaches experienced a worsening of her symptoms at the onset of her pregnancy. A magnetic resonance imaging (MRI) in the first trimester revealed increased ventricular dilation, indicating an obstructive cause due to aqueduct stenosis. During a neurosurgical board meeting, treatment options were discussed, considering the identifiable obstruction, the heightened intra-abdominal pressure associated with pregnancy, and the risk of ventricular shunt dysfunction. The patient underwent an endoscopic third ventriculostomy (ETV) without complications, leading to both symptom relief and a successful conclusion to the pregnancy.Discussion Neurosurgical procedures in pregnant women are uncommon due to the increased risks to both the mother and the fetus. However, when performed by a qualified multidisciplinary team, they can lead to positive outcomes. In cases of hydrocephalus during pregnancy, ETV appears to be a viable alternative for surgical intervention, particularly when hydrocephalus becomes symptomatic and an obstructive cause is identified, whether in patients with existing shunts or those with newly developed hydrocephalus.
Keywords: obstructive hydrocephalus; pregnancy; endoscopic third ventriculostomy; ventriculoperitoneal shunt; case report